2015
DOI: 10.1073/pnas.1506299112
|View full text |Cite
|
Sign up to set email alerts
|

A self-lysis pathway that enhances the virulence of a pathogenic bacterium

Abstract: In mammalian cells, programmed cell death (PCD) plays important roles in development, in the removal of damaged cells, and in fighting bacterial infections. Although widespread among multicellular organisms, there are relatively few documented instances of PCD in bacteria. Here we describe a potential PCD pathway in Pseudomonas aeruginosa that enhances the ability of the bacterium to cause disease in a lung infection model. Activation of the system can occur in a subset of cells in response to DNA damage throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 44 publications
2
58
0
1
Order By: Relevance
“…We found two genes of the alpBCDE lysis cassette, alpB and alpC , were repressed by RhlR in E90 under the conditions of our experiments. While induction of alpBCDE , via de-repression of the alpA gene, has been shown to be lethal to individual cells, it may benefit infecting cells at the population level [39]. We also observed down-regulation of the gene encoding the posttranscriptional regulatory protein RsmA by RhlR in E90.…”
Section: Resultsmentioning
confidence: 63%
“…We found two genes of the alpBCDE lysis cassette, alpB and alpC , were repressed by RhlR in E90 under the conditions of our experiments. While induction of alpBCDE , via de-repression of the alpA gene, has been shown to be lethal to individual cells, it may benefit infecting cells at the population level [39]. We also observed down-regulation of the gene encoding the posttranscriptional regulatory protein RsmA by RhlR in E90.…”
Section: Resultsmentioning
confidence: 63%
“…Indeed, the lysis of the mother cell at the end of sporulation represents an example of programmed cell death in a simple multicellular organism (the sporangium, consisting of just two cells: the mother cell and forespore). The existence of such altruistic examples of regulated cell death in independently growing bacteria and single-celled eukaryotes, though, has been controversial (5658), especially since manifestations of this phenomenon are usually reported as a stress response of cells to an environmental insult rather than as a normal part of the cell cycle (5961). A recent example of programmed cell death identified in the unicellular yeast Saccharomyces cerevisiae , though, suggested that during gametogenesis (also referred to as sporulation) aborted meiotic products that naturally arise are actively destroyed in a fashion that exhibits several key features of eukaryotic apoptosis, including genome fragmentation, in an effort to preserve the integrity of the germline (62).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports of “apoptotic-like” cell death in bacterial cells have added to the changing view of bacterial communities as more than simply a collection of independently operating cells, leading to speculation that unicellular organisms may initiate cell death to benefit the population as a whole (Bos et al, 2012; Dwyer et al, 2012; McFarland et al, 2015). Although specific mechanisms for cell death in these cases have been well characterized, the exact benefit of such an act to a single-celled organism has sometimes been difficult to explicitly demonstrate.…”
Section: Discussionmentioning
confidence: 99%